2021
DOI: 10.3390/su132111831
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation and Convergence toward the 2030 Agenda’s Sustainability Development Goals: Evidence from Italian Listed Firms

Abstract: The United Nations 2030 Agenda has emphasized the potential of digital technology to enhance sustainability performance, assuming that digital transformation can enable firms’ convergence toward the Sustainable Development Goals. Despite this, the literature is unclear regarding whether there is a positive relationship between digitalization and sustainability, as the effects of digital transformation are controversial. The main goal of this study was to assess the hypothesis that digital technology contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 90 publications
(129 reference statements)
1
38
0
Order By: Relevance
“…This fact fully confirms that the strengthened multi-energy concern can contribute to the implementation of activities carried out in light of the 2030 Agenda. Thus, it can be considered that the scale of M and A transactions in the sector, which take place in the energy sector are due to signed agreements and are the result of actions carried out in light of the 2030 Agenda [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This fact fully confirms that the strengthened multi-energy concern can contribute to the implementation of activities carried out in light of the 2030 Agenda. Thus, it can be considered that the scale of M and A transactions in the sector, which take place in the energy sector are due to signed agreements and are the result of actions carried out in light of the 2030 Agenda [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the 2030 Agenda for Sustainable Development, adopting the EU Renewable Energy Directive and the European Green Deal, the European Union aims for the extremely ambitious goal to become climate neutral by 2050 [7][8][9][10][11][12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DT is a strong partial mediator between CSR attributes and CSR authenticity (Liu and Jung, 2021). In addition, Camodeca and Almici (2021) found that digital technologies significantly improve ESG and help companies to achieve Sustainability Development Goals. In terms of supply chain, the use of big data analytics by firms can positively moderate the relationship between sustainable supply chain management and organizational performance (Zhu et al, 2022).…”
Section: Dt and Cemmentioning
confidence: 98%